Inorganic salts resistance associated with a lactose-fermenting plasmid in Streptococcus lactis. - Efstathiou, J D (1977)
Present evidence indicates that lactose metabolism in group N streptococci is linked to plasmid deoxyribonucleic acid. Lactose-positive (Lac+) Streptococcus lactis and lactose-negative (Lac-) derivatives were examined for their resistance to various inorganic ions. Lac+ S. lactis strains ML3, M18, and C2 were found more resistant to arsenate (7.5- to 60.2-fold), arsenite (2.25- to 3.0-fold), and chromate (6.6- to 9.4-fold), but more sensitive to copper (10.0- to 13.3-fold) than their Lac- derivatives. These results suggested that genetic information for resistance and/or sensitivity to these ions resides on the "lactose plasmid." Kinetics of ultraviolet irradiation inactivation of transducing ability for lactose metabolism and arsenate resistance confirmed the plasmid location of the two markers. Lac+ transductants from S. lactis C2 received genetic determinants for resistance to arsenate, arsenite, and chromate but not for copper sensitivity. In this case, resistance markers were lost when the transductants became Lac- but the derivatives remained copper resistant. The resistant markers for arsenate and arsenite could not be identified as separate genetic loci, but chromate resistance and copper sensitivity markers were found to be independent genetic loci. The "lactose plasmid" from S. lactis C10 possessed the genetic loci for arsenate and arsenite resistance but not for chromate resistance or copper sensitivity.